The role of technology in clinician-to-clinician communication. Issue 12 (19th July 2013) - McElroy, Lisa M; Ladner, Daniela P; Holl, Jane L
Abstract : Incomplete, fragmented and poorly organised communications contribute to more than half the errors that lead to adverse and sentinel events. Meanwhile, communication software and devices with expanding capabilities are rapidly proliferating and being introduced into the healthcare setting. Clinicians face a large communication burden, which has been exacerbated by the additional challenge of selecting a mode of communication. In addition to specific communication devices, some hospitals have implemented advanced technological systems to assist with communication. However, few studies have provided empirical evidence of the specific advantages and disadvantages of the different devices used for communication. Given the increasing quantities of information transmitted to and by clinicians, evaluations of how communication methods and devices can improve the quality, safety and outcomes of healthcare are needed.